PENGARUH PENGGANTIAN SEBAGIAN RANSUM DENGAN TEPUNG DAUN DAN BATANG UBI JALAR (Ipomoea batatas) TERHADAP KECERNAAN PROTEIN DAN ENERGI PADA TERNAK BABI - Salea, Hendro F. V.; Najoan, M.; Umboh, J. F.; Pontoh, C.J. (Universitas Sam Ratulangi, 2018)
EFFECT OF PARTLY SUBSTITUTION OF BASAL DIET WITH SWEET POTATO VINES (Ipomoea batatas) MEAL ON ENERGY AND PROTEIN DIGESTIBILITY OF PIGS. Pork is one of the meat producer animals that can contribute to satisfy animal protein requirements. Sweet potato vines is considered as an agricultural waste product and can be used as feedstuff for pigs. The present study was conducted to determine the utilization of sweet potato vines substituting basal diet on energy and protein digestibility of finisher pigs. Five ‘Duroc X Spotted Poland China’ castrated male pigs, aged 3.5 to 4.0 months with an initial body weight 50 kg (±2.5 kg) were assigned to four treatments as follow: R0 = 100% basal diet + 0% sweet potato vines meal; R1 = 92.5% basal diet + 7.5% sweet potato vines meal; R2 = 85% basal diet + 15% sweet potato vines meal; R3 = 77.5% basal diet + 22.5% sweet potato vines meal; and R4 = 70% basal diet + 30% sweet potato vines meal. Parameters measured were: energy and protein digestibility. Research reasults showed that there is no significant differences (P > 0.05) among treatments on energy and protein digestibility of pigs in the present study. This indicated that utilization of sweet potato vines meal up to 30% replacing basal diet did not affect digestible energy and protein of finishing pigs. It can be concluded that substituting basal diet with sweet potato vines meal up to 30% has no negative effect on energy and protein digestibility of finishing pigs. Keywords: Sweet potato vines, energy digestibility, protein digestibility, pigs